Sistematización del proceso de medición de clima laboral en la empresa Tiw de Venezuela S.A. - Carrillo Gonzáles, Bethsabé Alejandra (2018)
The current Project, establishes the systematization of the design experience of a methodology that will measure the working environment and planning of an improvement plan for the company TIW DE VENEZUELA S.A. located in Quito Metropolitan District. The systematization Will be focused on the intervention work performed, based on statistical instruments like observation, interviews and surveys. The assessed universe corresponded 85% of the total workers of TIW DE VENEZUELA S.A. which were 71 employees. The application of the survey determined that the dimensions to be improved included performance and recognition. The present work is relevant because through the experience it was possible to relate the theoretical knowledge obtained in the career of Psychology with the practical professional practice. In addition, the relevance of the participation of a work psychologist inside the company was established. The impulse that motivated the present systematization was to contribute with the evaluation of the working environment of TIW DE VENEZUELA S.A. and with the information obtained, suggest a plan to improve the work climate that increases the satisfaction of workers in the company and therefore their productivity.